Personality Traits as Predictors of Depression, Anxiety and Stress with Secondary School Students of Final Years - Vujičić, Milena M.; Ranđelović, Dušan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The main aim of this research is to examine the predictive power of personality traits, as defined by the Big five model of personality in expressing depression, anxiety, and stress with secondary school students of final years. The research was conducted on a sample of 977 secondary school students in the third and fourth grade from ten secondary schools in Niš. The gender structure of the sample was as follows: 397 boys and 607 girls. The following instruments were used in the research: Depression Anxiety Stress Scales (DASS-21; Lovibond and Lovibond, 1995), Big Five Inventory – BFI (John, Donahue and Kentle, 1991). The results showed that the regression model constructed by personal traits (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to experience) explain 26% of the criterion variable of Anxiety. The largest individual contribution to the prediction of this variable is achieved by the personal trait Neuroticism (β=.34, p
Keywords: secondary school students; stress; anxiety; depression; personality traits